(untitled) (Clinics, 2008)
INTRODUCTION: Somatosensory stimulation of the paretic upper limb enhances motor performance and excitability in the affected hemisphere, and increases activity in the unaffected hemisphere, in chronic stroke patients. We tested the hypothesis that somatosensory stimulation of the paretic hand would lead to changes in excitability of the unaffected hemisphere in these patients, and we investigated the relation between motor function of the paretic hand and excitability of the unaffected hemisphere. METHODS: Transcranial magnetic stimulation was administered to the unaffected hemisphere of nine chronic stroke patients. Patients were submitted to 2-h somatosensory stimulation in the form of median nerve stimulation and control stimulation using a cross-over design. Baseline Jebsen-Taylor test scores were evaluated. Resting motor threshold, intracortical facilitation, short-interval intracortical inhibition, and visual analog scores for attention, fatigue and drowsiness were measured across conditions. RESULTS: Better pre-stimulation baseline motor function was correlated with deeper SICI in the unaffected hemisphere. We found no overt changes in any physiological marker after somatosensory stimulation. There was increased drowsiness in the control session, which may have led to changes in intracortical facilitation. CONCLUSIONS: Our results do not support an overt effect of a single session of somatosensory stimulation of the paretic hand on motor cortical excitability of the unaffected hemisphere as measured by motor threshold, short-interval intracortical inhibition or intracortical facilitation. It remains to be determined if other markers of cortical excitability are modulated by somatosensory stimulation, and whether repeated sessions or lesion location may lead to different effects.